Endoscopic treatment of biliary complications after duct-to-duct biliary anastomosis in pediatric liver transplantation - Harputluoglu, M.; Demirel, U.; Caliskan, A. R.; Selimoglu, A.; Bilgic, Y.; Aladag, M.; Yilmaz, S. (Springer, 2019)
Background Studies reporting outcomes of endoscopic treatment methods in children who underwent liver transplantation (LT) is very limited. We present our outcomes, as a high-volume transplant center where endoscopic methods are preferred as the first choice in the treatment of biliary complications in children. Methods Patients who underwent endoscopic retrograde cholangiopancreatography (ERCP) as the first treatment approach for biliary complications after LT between 2005 and 2017 were included. Clinical data included patient demographics, ERCP indications (stricture or leak), and treatment outcomes, including the need for percutaneous and surgical intervention. Results ERCP was performed in 49 patients who had a duct-to-duct anastomosis (38 living donor liver transplantation (LDLT), 11 deceased donor liver transplantation (DDLT)). The most common biliary complication was stricture. Our endoscopic success rate was 66.7% (18/27) and 75% (6/8) in LDLT and DDLT patients with stricture (p > 0.05), respectively. While our endoscopic success rate was 75% (3/4) in patients with leak alone after LDLT, it was 25% (1/4) in patients with leak and stricture in this group. The endoscopic success rate was 50% in two patients who had leak alone after DDLT. Conclusions ERCP should be considered as a preferential treatment option for the management of biliary complications in pediatric liver transplant patients with duct-to-duct anastomosis, as in adults.
Keywords: Pediatrics; Liver transplantation; Biliary complications; Endoscopic retrograde cholangiopancreatography